In situ construction of protonated g-C3N4/Ti3C2 MXene Schottky heterojunctions for efficient photocatalytic hydrogen production - Xu, Haotian; Xiao, Rong; Huang, Jingran; Jiang, Yan; Zhao, Chengxiao; Yang, Xiaofei (Chinese journal of catalysis, 2021)
Converting sustainable solar energy into hydrogen energy over semiconductor-based photocatalytic materials provides an alternative to fossil fuel consumption. However, efficient photocatalytic splitting of water to realize carbon-free hydrogen production remains a challenge. Heterojunction photocatalysts with well-defined dimensionality and perfectly matched interfaces are promising for achieving highly efficient solar-to-hydrogen conversion. Herein, we report the fabrication of a novel type of protonated graphitic carbon nitride (PCN)/Ti3C2 MXene heterojunctions with strong interfacial interactions. As expected, the two-dimensional (2D) PCN/2D Ti3C2 MXene interface heterojunction achieves a highly improved hydrogen evolution rate (2181 μmol·g−1) in comparison with bulk g-C3N4 (393 μmol·g−1) and protonated g-C3N4 (816 μmol·g−1). The charge-regulated surfaces of PCN and the accelerated charge transport at the face-to-face 2D/2D Schottky heterojunction interface are the major contributors to the excellent hydrogen evolution performance of the composite photocatalyst. In addition to the protonation of graphitic carbon nitride, conductive 2D MXene was introduced as a co-catalyst to further accelerate electron-hole separation and interfacial charge transport for improved hydrogen production.